Graphene-based nanoprobes for molecular diagnostics. Issue 19 (7th October 2015) - Chen, Shixing; Li, Fuwu; Fan, Chunhai; Song, Shiping
<x xml:space="preserve">Abstract</x> This review focuses on the construction of graphene-based nanoprobes and their use for the detection of various bioactive molecules in molecular diagnostics.